Analisis dan Implementasi Sistem Pengelolaan Keuangan dan Akuntansi berbasis Software Accurate pada Asrama Indonesia Quran Foundation - Cica Nur Latifah; Suhendi Suhendi (Jurnal Informatika Terpadu, 2020)
Indonesia Quran Foundation is a foundation engaged in Quran-based youth education. Along with the development, this foundation has increased very rapidly and is included in its financial management. The results of an interview with the Indonesian Quran Foundation Dormitory Treasurer stated that currently the Indonesian Quran Foundation Dormitory is still using manual recording using Microsoft Excel. This manual recording starts from recording the receipt of tuition fees for mahasantri to the financial reports. Based on this, technology is needed to facilitate recording and preparation of accurate financial reports. Therefore, an accounting information system is needed. An Accounting Information System (AIS) is a collection of resources, such as people and tools designed to convert financial and other data into information. In this research, the accounting information system applied is Accurate Accounting Software. Accurate Accounting Software is an accounting and finance program designed to meet the needs of companies in terms of accounting and financial records. The author implements the Accurate application at the Indonesia Quran Foundation Dormitory by going through several series of stages. Starting from a preliminary study, conducting analysis, implementation, testing with the black-box method, to the results of evaluation and improvement. The application of the tuition fee payment system to financial reports at the Indonesian Quran Foundation dormitory has been successfully carried out into the invoice stage and as evidence of financial reports to the Indonesia Quran Foundation foundation.